Knowledge management and equipment reliability: towards a relationship model. (1st January 2012) - Pyne, Tarapada; Baul, Utpal; Jangid, Radhey Shyam
Initial research studies on the knowledge (K)/knowledge management (KM) were centred on the development of the depth of the subject and of academic nature. There was no attempt, however, to link KM and organisational performance till the relevant research to investigate the relationship between KM and business performance especially in nuclear plants. Researches and the surveys in early this century showed few attempts to focus the role of KM in management of engineering assets/equipments. The past literature concentrated towards creating KM maturity models applicable to either the stages or on the process of implementation or on the process-capability. This study attempts to develop first a validated KM instrument, then to prove linkage of organisation's various failure factors of KM with equipment performance. Interplay and inter-dependence of the failure factors are analysed along-with various independent factors those have bearing on equipment failure. Relationship of these independent factors with associated knowledge gap and/or knowledge risk and/or knowledge strength has guided then to formulate equipment-oriented KM strategy and the proposed 'relationship' and 'solution' models. Thus, a new frontier of KM, yet to be tapped, that has the specific relation to reliability is evolved.